Absence of hantavirus in water voles and Eurasian beavers in Britain. (23rd February 2019) - Girling, Simon Justin; McElhinney, Lorraine M; Fraser, Mary A; Gow, Derek; Pizzi, Romain; Naylor, Adam; Cole, Georgina; Brown, Donna; Rosell, Frank; Schwab, Gerhard; Campbell‐Palmer, Roisin
Abstract : Hantaviruses are RNA viruses (order Bunyavirales, family Hantaviridae ) found in rodent, bat and insectivore reservoir‐hosts and have been reported as an emerging significant zoonotic risk in Europe. As part of two native semiaquatic rodent restoration projects, tissue and urine samples were tested for hantavirus from water voles ( Arvicola amphibius ) (n=26, in 2015) and Eurasian beavers ( Castor fiber ) (n=20, covering 2010–2015) using a pan‐hantavirus nested real‐time PCR test. Kidney and lung samples were also analysed by light microscopy after haematoxylin and eosin staining of formalin‐fixed paraffin wax sections. Individuals selected included those forming the source of release animals and from those already free‐living in Britain in areas targeted for release, to identify existing reservoirs. For water voles all tested individuals were from Britain (n=26); for beavers some were from Britain (Scotland) (n=9) and some were samples from wild Norwegian (Telemark region) (n=6) and German (Bavaria region) animals (n=5) that formed the source of accepted wild populations currently present in Scotland. All samples tested from both species were negative for hantavirus RNA and showed no significant histopathological changes suggesting that reservoir infection with hantavirus in water voles in Britain and Eurasian beavers present in Britain, Norway and Bavaria, Germany, is unlikely.